Absorptive capacity and performance in Malaysian manufacturing SMEs / Zarina Denan - Denan, Zarina (2011)
Many small and medium-sized enterprises (SMEs) presently evolve in a complex business environment characterized by globalization the internationalization of markets and the need for greater efficiency effectiveness and competitiveness based on innovation and knowledge. This has put increasing pressure upon the management of these firms especially manufacturing and technological SMEs that must now compete globally. Many entrepreneurial researches have highlighted the significance of potential strategies, technological innovation, or entrepreneurial orientation in improving SMEs productivity. However, a few have identified the SMEs capabilities in knowledge process leading to excellent business performance. This research is concerned with identifying those answers through various knowledge capabilities that small business in Malaysia can adopt to enhance their performance, by employing the knowledge-based view approach. SMEs represent more than 95% of total manufacturing establishments in Malaysia, 75% of which encompasses textiles and apparel sector, food and beverages, metal and metal products, publishing, printing and reproducing of recorded media, furniture sector, rubber and plastics products and wood and wood products industry. Questionnaires were personally administered to 180 companies belonging to the above industries. Simple, multiple and hierarchical regression analyses were performed to examine relationships among the variables under study. The simple regression analysis suggested a significant and positive relationship between SMEs owners/managers' prior knowledge and absorptive capacity. The results also indicated that there was a significant and positive relationship between the SMEs owners/managers' prior knowledge and absorptive capacity. A positive and significant relationship between absorptive capacity and financial performance was also found. The other two performances (operational and innovation were found to have insignificant relationship with absorptive capacity. Hierarchical regression was utilized to test the impact of moderating variables, environmental dynamism, strategic planning formality and strategic decision making process on absorptive capacity-performance relationship. The study highlighted only strategic decision making process had some impact on absorptive capacity-operational performance relationship. The study also obtained significant and negative effect of strategic decision making process on absorptive capacity-innovation performance relationship. In summary, findings highlighted the importance of SMEs to develop their own knowledge-based not only for survival but to have sustainable competitive advantage.